The diplomatic corps and the authoritarian regime (1926-1974) - Aires Oliveira, Pedro (2006)
This article seeks to describe one of the elite bodies in the Portuguese state - diplomats - between 1926 and 1974. The first part describes the policies of republican governments towards the Ministry of Foreign Affairs and the impact of the revolution of 28 May 1926 on the apparatus of diplomacy. The second part looks at how governments under the military dictatorship and the Estado Novo sought to structure the diplomatic profession. Then, based on biographical data, we draw a social and political outline of the diplomatic corps for the period under study. The final section examines the relationship between Salazar's regime and the Ministry of Foreign Affairs, drawing parallels whenever possible with other European dictatorships (Franco 's Spain, fascist Italy and Nazi Germany).